(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
In the most general sense of the word, domestic violence is a combination of psychological, social, and economic factors that combine (or not) and create the preconditions or the atmosphere in which abuses occur in the form of physical, psychological, sexual, or economic violence towards the victims. Economic violence is a legally recognized form of domestic violence as defined in the new Law on prevention and protection from violence against women and domestic violence in force since January 2021. It often occurs in the context of intimate partner violence and involves the control of a partner or ex-partner’s money and finances. Economic violence can take many forms, such as property damage, restricting access to financial resources, education, or the labor market, or not complying with economic responsibilities, such as alimony. Women and girls are particularly vulnerable to this form of violence, especially in countries with a strong patriarchal mentality such as North Macedonia. The years of transition affected the deterioration of the economic situation for many families and influenced the increase of the economic dependence of the woman on the man, and at the same time confronted women and families with a new system of relations, norms, and values. This paper aims to analyze the factors that influence the emergence of economic violence against women in North Macedonia.